The Effect of Key Audit Matters on Audit Quality, Audit Fee, and Audit Report Lag (Empirical Study on IDX listed company from 2021-2022) - Perdana, Laudza Indra; Raharja, Surya (Westscience Press, 2024)
This study aims to examine the effect of key audit matters on audit quality, audit fees, and audit report lag. Key audit matters is an independent variable, then the audit quality, audit fees, and audit report lag as dependent variables. This study adds firm size, profitability, solvability, audit committee size and big4 audit firms as control variables. The sample selected in this study were all non-financial sector companies listed on IDX in 2021-2022 with total sample 1024 company samples. The selection of samples used purposive sampling approach with criteria and prerequisites that have been determined by the author. Hypothesis analysis used by researchers in testing the hypothesis is multiple linear regression analysis. The results of the study obtained results that application of key audit matters has a significant effect on improving the quality of financial report audits. The application of key audit matters also has a significant negative effect on audit report lag. The main cause of the decrease in audit duration is not due to the application of key audit matters, but the revocation of the relaxation limit for financial report reporting. Finally, the application of key audit matters does not have a significant effect on audit fee.